Some Of The Features Of The Educational Curriculum In The Holy Qur’an (Journal of Human Sciences, 2021)
The study aimed to demonstrate the importance of the educational curriculum in the Holy Qur’an, and that it is the only curriculum that can keep pace with the development of human life, from the beginning of its life to its end, because it is a divine approach that relies on divine foundations, characteristics and methods, through which the nation can be built in a solid and strong building; Because it develops the behavior of the individual and promotes it towards higher values, and helps him to acquire the patterns of behavior that he must behave in various life situations. It also contributes to the development of individuals and works to develop their scientific and practical skills, so that the society raise new generations on it.